Nerva and the Roman succession crisis of AD 96-99 - Grainger, John D., 1939- (Roman imperial biographies., 2003)
This much needed study addresses the problems of Domitian's assassination, and fills an important gap in the literature on Roman imperial history by providing a detailed assessment of Nerva's rule.